2018
DOI: 10.1007/s00595-018-1661-8
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer with perforation

Abstract: Perforation of the colon is a rare complication for patients with colon cancer and usually requires emergent surgery. The characteristics of perforation differ based on the site of perforation, presenting as either perforation at the cancer site or perforation proximal to the cancer site. Peritonitis due to perforation tends to be more severe in cases of perforation proximal to the cancer site; however, the difference in the outcome between the two types remains unclear. Surgical treatment of colon cancer with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 63 publications
0
35
1
15
Order By: Relevance
“…Intestinal perforation at the time of diagnosis is not a significant risk factor for relapse, as our study shows, against to other studies in the literature (6,(25)(26)(27)(28). The risk of relapse is 2 times greater for patients with perforation compared to nonperforated cases, and is higher in the first 30 months post-op, eventually the survival curves getting close to each other, being almost similar at 60 months post-op.…”
Section: Discussioncontrasting
confidence: 53%
“…Intestinal perforation at the time of diagnosis is not a significant risk factor for relapse, as our study shows, against to other studies in the literature (6,(25)(26)(27)(28). The risk of relapse is 2 times greater for patients with perforation compared to nonperforated cases, and is higher in the first 30 months post-op, eventually the survival curves getting close to each other, being almost similar at 60 months post-op.…”
Section: Discussioncontrasting
confidence: 53%
“…Tumour or bowel perforation is considered a highrisk factor for Stage II colorectal cancer and the current review found a benefit in overall survival with adjuvant chemotherapy in patients who had undergone emergency surgery for bowel obstruction or perforation. Other studies also suggested that adjuvant chemotherapy improves the long-term prognosis of perforated colorectal cancer [57,58] and recommended adjuvant chemotherapy for Stage III and high-risk Stage II colon cancer with perforation [25]. Similarly, Chen et al [59] evaluated the outcomes of colon cancer with perforation or obstruction and showed that the tumour stage was a risk factor, while receiving adjuvant chemotherapy or radiotherapy was a protective factor, in their multivariate analysis of the overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour or bowel perforation is considered a high‐risk factor for Stage II colorectal cancer and the current review found a benefit in overall survival with adjuvant chemotherapy in patients who had undergone emergency surgery for bowel obstruction or perforation. Other studies also suggested that adjuvant chemotherapy improves the long‐term prognosis of perforated colorectal cancer [57,58] and recommended adjuvant chemotherapy for Stage III and high‐risk Stage II colon cancer with perforation [25]. Similarly, Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Malignancy is the commonest cause, accounting for 36% of perforations [48]. Perforation may also be iatrogenic (20%), diverticula-related (19%) and less commonly due to trauma, foreign body ingestion, faecal impaction, ischemia, inflammatory bowel disease, endometriosis, connective tissue disease, radiotherapy, drugs and spontaneous [4,6,7,10,11,49]. The site of perforation is often linked with its cause [4,8,10]; therefore, neoplastic, spontaneous, diverticular (in western countries), blunt trauma and ischemic perforations commonly occur on the left side of colon, whereas inflammatory bowel disease, diverticulitis (in eastern countries) and penetrating trauma perforations tend to be right-sided.…”
Section: Colorectal Perforationmentioning
confidence: 99%
“…Perforation complicates 2.6-10% of colon cancers, occurring most commonly in the sigmoid colon (47.3%) and cecum (24.8%) [2,6,11,49,51]. Two mechanisms are recognised [2,4,6,11,49]: the first consists of tumour necrosis and subsequent perforation at the tumour site. The second occurs proximal to the malignancy, as a result of bowel distension secondary to obstruction, frequently occurs at the cecum and usually leads to massive pneumoperitoneum (Fig.…”
Section: Colorectal Perforationmentioning
confidence: 99%